Does curcumin or metformin attenuate oxidative stress and diabetic nephropathy in rats? - Soheila Asadi; Mohammad Taghi Goodarzi; Jamshid Karimi; Mohammad Hashemnia; Iraj Khodadadi (Society of Diabetic Nephropathy Prevention, 2019)
Background: Since the importance of oxidative stress in the development of diabetic nephropathy (DN) has previously been established, the therapeutic effects of various natural antioxidant agents or synthetic drugs have so far been investigated. Objectives: The aim of this study was to investigate the beneficial effects of curcumin (a natural polyphenol) and metformin (a common therapeutic medicine for type 2 diabetes) on oxidative status in kidney of type 1 diabetic rats. Materials and Methods: In this experimental study 60 male Wistar rats were divided into 10 groups. Type 1 diabetes was induced by streptozotocin. Rats received chow diet and treated with either normal saline in control (N) and diabetic control (D) groups or different doses of metformin (Met) (300 or 500 mg/kg body weight) or curcumin (Cur) (50 or 150 mg/kg body weight) in N+Met300, N+Met500, N+Cur50, N+Cur150, D+Met300, D+Met500, D+Cur50, and D+Cur150 groups. Urinary creatinine, urea, and protein were measured. Total antioxidant capacity (TAC), total oxidant status (TOS), malondialdehyde (MDA), and the activity of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase were assessed in kidney tissues. Results: Both metformin and curcumin showed significant effects on urinary creatinine, urea, and protein levels (P value for all was <0.001). Unlike metformin, curcumin completely restored TAC and TOS (P<0.001), and MDA (P=0.012) in kidney tissues and significantly recovered the activities of SOD (P= 0.003), GPx (P< 0.001), and catalase (P=0.011). Conclusions: Curcumin was found more effective than metformin in attenuating oxidative status in DN.